Fifth International Conference on 3-D Digital Imaging and Modeling (3DIM'05)
DOI: 10.1109/3dim.2005.31
|View full text |Cite
|
Sign up to set email alerts
|

Determining Characteristic Views of a 3D Object by Visual Hulls and Hausdorff Distance

Abstract: Nowadays, with the exponential growing of 3D object representations in private databases or on the web, it is all the more required to match these objects from some views. To improve the results of their matching, we work on the characteristic views of an object. The aim of this study is to find how many characteristic views are required and what relative positions are optimal. This is the reason why the visual hulls are used. From some 2D masks, the nearest possible 3D mesh from the original object is compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This domain has numerous applications in the real world such as a robotics, artificial intelligence and more [1][2][3]. Many approaches have been proposed [4][5]. The first one is to use the characteristic views of 3D object for feature extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This domain has numerous applications in the real world such as a robotics, artificial intelligence and more [1][2][3]. Many approaches have been proposed [4][5]. The first one is to use the characteristic views of 3D object for feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is most often taken in the recognition systems of 3D objects. D. Naji al [4] have proposed a method based on the characterization of 3D objects by a set of 7 characteristic views, A.Theetten& al [5] used the visual hulls to find how many characteristic views are required and what relative positions are optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Content-based description plays a prominent role in indexing and retrieval [1][2][3][4]. It is therefore important to develop invariant representations for 3D objects.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to develop invariant representations for 3D objects. An excellent review about indexing and retrieval of 3D objects can be found in [1][2][3]. As can be seen from this review, most of the proposed techniques are invariant under a very limited class of transformations, for example, translations, scaling, and rotations.…”
Section: Introductionmentioning
confidence: 99%